Support Effects on Thiophene Hydrodesulfurization over Co-Mo-Ni/Al2O3 and Co-Mo-Ni/TiO2-Al2O3 Catalysts - 刘超 周志明 黄永利 程振民 袁渭康 (Chinese journal of chemical engineering, 2014)
A carbon-based sulfonated catalyst was prepared by direct sulfonation and carbonization （in moderate conditions：200 ＆#176;C, 12 h） of red liquor solids, a by-product of paper-making process. The prepared sulfonated cata-lyst （SC） had aromatic structure, composed of carbon enriched inner core, and oxygen-containing （SO3H, COOH, OH） groups enriched surface. The SO3H, COOH, OH groups amounted to 0.74 mmol·g^-1, 0.78 mmol·g^-1, 2.18 mmol·g^-1, respectively. The fresh SC showed much higher catalytic activity than that of the traditional solid acid catalysts （strong-acid 732 cation exchange resin, hydrogen type zeolite socony mobile-five （HZSM-5）, sulfated zir-conia） in esterification of oleic acid. SC was deactivated during the reactions, through the mechanisms of leaching of sulfonated species and formation of sulfonate esters. Two regeneration methods were developed, and the catalytic activity can be mostly regenerated by regeneration Method 1 and be fully regenerated by regeneration Method 2, respectively.